Cost of neonatal care. Issue 3 (March 1988) - Ryan, S; Sics, A; Congdon, P
Abstract : A six month evaluation of the costs of a regional neonatal medical and surgical unit was carried out. The total cost for six months was pounds 970, 000 and this covered 4349 inpatient days and 282 admissions. For medical cases the cost ranged from pounds 132 to pounds 27, 600 and the mean daily cost for different weight groups ranged from pounds 159 to pounds 274. The average daily cost for regional patients at pounds 258 was greater than for district patients who cost pounds 199. Altogether 23 medical patients weighing less than 1000 g at birth were admitted. The total cost for nine of these infants who died was pounds 30, 991-about 3% of the unit's total budget.